Future of SSI in Uttar Pradesh - Kumar Garg, Dr. Vinay (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
A Critical Evaluation and Future Outlook, Liberalization Effects on SSI (Small Scale Industry), Issues and Prospects In the context of the emerging scenario of liberalisation and the financial sector reforms the development banks need to gear themselves to meet the varied requirements of the small and medium scale sector. They need to create new products that are relevant and have more impact. In the new economic scenario, the role of technology has emerged as a strategic variable influencing manufacturing system of the industrial units who need to reorient their strategies to meet the challenges of the competition. With the upward revision of the investment ceiling, much potential has now been created for technological upgradation and the vertical integration of the industrial units so as to derive advantage from economies of scale. Key words- economic, industries, development, liberalization, infrastructure.